Economic Law Compliance in AI-Driven Digital Mompreneurship: The Role of Entrepreneurial Attitudes and Self-Efficacy in Performance - Romansyah Sahabuddin; Mahmuddin Mahmuddin; Ampauleng Ampauleng (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Website-based Artificial Intelligence (AI) transformation among mompreneurs has enhanced business performance opportunities; however, gaps in digital economic law compliance awareness persist. This study examines the effects of AI integration and entrepreneurial attitudes on mompreneur business performance, with self-efficacy as a mediating variable within an economic law compliance framework. A quantitative design employing Structural Equation Modeling (SEM) was applied to 400 MSME mompreneurs in Makassar City selected through purposive sampling. Data were collected using structured questionnaires measuring AI integration, entrepreneurial attitudes, self-efficacy, and business performance. Measurement model validation (loading, CR, AVE) and structural model estimation (β, t-value, p-value) were conducted alongside mediation analysis. SEM results reveal significant effects of AI integration on self-efficacy (β = 0.52), entrepreneurial attitudes on self-efficacy (β = 0.71), AI integration on business performance (β = 0.74), entrepreneurial attitudes on business performance (β = 0.83), and self-efficacy on business performance (β = 0.80). Findings confirm self-efficacy as a partial mediator strengthening technological and behavioral influences on performance outcomes. AI integration and entrepreneurial attitudes are primary predictors of mompreneur performance, with self-efficacy functioning as a reinforcing psychological mechanism. From an economic law perspective, effective AI adoption must be accompanied by compliance with electronic transaction, personal data protection, and MSME regulatory frameworks to ensure sustainable digital entrepreneurship. Policy initiatives should integrate AI capability development, entrepreneurial self-efficacy enhancement, and digital economic law compliance education for mompreneurs to foster productive and legally compliant MSME ecosystems.